2015
DOI: 10.1021/acs.inorgchem.5b00834
|View full text |Cite|
|
Sign up to set email alerts
|

Unsymmetrical Chelation of N-Thioether-Functionalized Bis(diphenylphosphino)amine-Type Ligands and Substituent Effects on the Nuclearity of Iron(II) Complexes: Structures, Magnetism, and Bonding

Abstract: Starting from the short-bite ligands N-thioether-functionalized bis(diphenylphosphino)amine-type (Ph2P)2N(CH2)3SMe (1) and (Ph2P)2N(p-C6H4)SMe (2), the Fe(II) complexes [FeCl2(1)]n (3), [FeCl2(2)]2 (4), [Fe(OAc)(1)2]PF6 (5), and [Fe(OAc)(2)2]PF6 (6) were synthesized and characterized by Fourier transform IR, mass spectrometry, elemental analysis, and also by X-ray diffraction for 3, 4, and 6. Complex 3 is a coordination polymer in which 1 acts as a P,P-pseudochelate and a (P,P),S-bridge, whereas 4 has a chlori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 115 publications
0
9
0
Order By: Relevance
“…Reactions between ligands 192 and 196 and FeCl 2 followed by recrystallization yielded complex 212 as a coordination polymer in which 192 acts simultaneously as a P,P-pseudochelate and a (P,P),S-bridge, while complex 213 has a chlorido-bridged dinuclear structure in which 196 acts only as a P,P-pseudochelate, as established by XRD analyses (Scheme and Table ). Since these complexes were obtained under strictly similar synthetic and crystallization conditions, the structural difference observed could only be ascribed to the different spacer between the N atom and the −SMe group. In both Fe­(II) complexes, one Fe–P bond was found to be unusually long [2.798(2) and 2.762(1) Å for 212 and 213 , respectively], and a theoretical analysis was performed [including a series of Fe complexes of general formula [FeCl 2 (SR 2 )­{R 2 1 PN­(R 2 )­PR 2 3 }] (R = H, Me; R 1 , R 2 , and R 3 = H, Me, Ph)] to unravel the electronic or steric reasons for this difference.…”
Section: Sulfur-based Functionalizationsmentioning
confidence: 99%
“…Reactions between ligands 192 and 196 and FeCl 2 followed by recrystallization yielded complex 212 as a coordination polymer in which 192 acts simultaneously as a P,P-pseudochelate and a (P,P),S-bridge, while complex 213 has a chlorido-bridged dinuclear structure in which 196 acts only as a P,P-pseudochelate, as established by XRD analyses (Scheme and Table ). Since these complexes were obtained under strictly similar synthetic and crystallization conditions, the structural difference observed could only be ascribed to the different spacer between the N atom and the −SMe group. In both Fe­(II) complexes, one Fe–P bond was found to be unusually long [2.798(2) and 2.762(1) Å for 212 and 213 , respectively], and a theoretical analysis was performed [including a series of Fe complexes of general formula [FeCl 2 (SR 2 )­{R 2 1 PN­(R 2 )­PR 2 3 }] (R = H, Me; R 1 , R 2 , and R 3 = H, Me, Ph)] to unravel the electronic or steric reasons for this difference.…”
Section: Sulfur-based Functionalizationsmentioning
confidence: 99%
“…Further indications that subtle changes in ligand design can strongly affect the nature of the resulting coordination complexes were also provided by the reactions between FeCl 2 and ligand 1 or 2 (1:1 molar ratio) since they led, under strictly similar reaction conditions, to an infinite coordination polymer or a dinuclear complex, respectively . It was concluded that electronic factors accounted for the unusual unsymmetrical chelation of the iron center (Chart , bottom), raising the question of a possible lability of phosphorus donors in solution, which is relevant to catalyst behavior.…”
Section: Introductionmentioning
confidence: 98%
“…10 Further indications that subtle changes in ligand design can strongly affect the nature of the resulting coordination complexes were also provided by the reactions between FeCl 2 and ligand 1 or 2 (1:1 molar ratio) since they led, under strictly similar reaction conditions, to an infinite coordination polymer or a dinuclear complex, respectively. 11 It was concluded that electronic factors accounted for the unusual unsymmetrical chelation of the iron center (Chart 1, bottom), raising the question of a possible lability of phosphorus donors in solution, which is relevant to catalyst behavior. Whereas studies on the coordination chemistry of DPPA-type ligands have mostly focused on metals of groups 6, 10, and 11, Ru and Rh, 5,12 those on Fe and Co remain scarce, although these earth-abundant metals are of considerable current interest and display versatile coordination spheres (coordination numbers and geometries) associated with diverse chemical and physical properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several bis(phosphino)amine ligands as well as their complexes have been studied in a wide range of catalytic processes [ 1 ], particularly in ethylene oligo/polymerization [ 11 ] and C–C cross coupling reactions [ 12 ]. These ligands are also used as assembling ligands for the formation of multinuclear complexes, due to the multiple donor atoms [ 13 ], and some of them and their derivatives have also found applications in surface and materials sciences [ 14 , 15 ]. Moreover, the chalcogenide forms of this type of ligands are also becoming increasingly important in view of their potential applications in catalysis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%